The effects of MyD88 deficiency on disease phenotype in dysferlin‐deficient A/J mice: role of endogenous TLR ligands. Issue 2 (10th September 2013) - Uaesoontrachoon, Kitipong; Cha, Hee‐Jae; Ampong, Beryl; Sali, Arpana; Vandermeulen, Jack; Wei, Benjamin; Creeden, Brittany; Huynh, Tony; Quinn, James; Tatem, Kathleen; Rayavarapu, Sree; Hoffman, Eric P; et al.
Abstract: An absence of dysferlin leads to activation of innate immune receptors such as Toll‐like receptors (TLRs) and skeletal muscle inflammation. Myeloid differentiation primary response gene 88 (MyD88) is a key mediator of TLR‐dependent innate immune signalling. We hypothesized that endogenous TLR ligands released from the leaking dysferlin‐deficient muscle fibres engage TLRs on muscle and immune cells and contribute to disease progression. To test this hypothesis, we generated and characterized dysferlin and MyD88 double‐deficient mice. Double‐deficient mice exhibited improved body weight, grip strength, and maximum muscle contractile force at 6–8 months of age when compared to MyD88‐sufficient, dysferlin‐deficient A/J mice. Double‐deficient mice also showed a decrease in total fibre number, which contributed to the observed increase in the number of central nuclei/fibres. These results indicate that there was less regeneration in the double‐deficient mice. We next tested the hypothesis that endogenous ligands, such as single‐stranded ribonucleic acids (ssRNAs), released from damaged muscle cells bind to TLR‐7/8 and perpetuate the disease progression. We found that injection of ssRNA into the skeletal muscle of pre‐symptomatic mice (2 months old) resulted in a significant increase in degenerative fibres, inflammation, and regenerating fibres in A/J mice. In contrast, characteristic histological features were significantly decreased in double‐deficient mice. These data point to a clear role for the TLR pathway in the pathogenesis of dysferlin deficiency and suggest that TLR‐7/8 antagonists may have therapeutic value in this disease. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.